PERAN DESA MANDIRI BENIH MENDUKUNG PERCEPATAN ADOPSI TEKNOLOGI VARIETAS UNGGUL BARU PADI (Forum Penelitian Agro Ekonomi, 2022)
Agricultural research and development agencies have produced several new, improved rice varieties (NIRVs) over the past few years with various advantages to dealing with climate change and increasing rice production. However, until now, the adoption of NIRVs is still relatively low. This paper aims to determine the performance and problems of adopting NIRVs and recommend strategies for accelerating the adoption of NIRVs by increasing seed availability through Seed Mandiri Village. This paper is the result of a review of several research results and relevant literature. Of the many released NIRVs, until now, their distribution is still minimal. Most farmers still use improved rice varieties that have been released for a long time, such as Ciherang, Mekongga, and IR64. The low availability of NIRV seeds on a commercial scale is one of the inhibiting factors for the adoption and spread of NIRVs. Optimizing the role of the Seed Self-Reliant Village can increase the availability of NIRV seeds. Seed Self-Reliant Villages in various regions can be encouraged to carry out sustainable breeding of NIRV seeds, especially for location-specific NIRV seeds. Thus, these efforts are expected to be able to increase the adoption of NIRVs to have further implications for increasing rice production and meeting national food needs.
Keywords: adoption; new improved rice varieties (NIRVs); Seed Self-Reliant Village; adopsi teknologi; Desa Mandiri Benih; varietas unggul baru (VUB) padi